1986
DOI: 10.1093/ajcn/44.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in rats with diet-induced obesity

Abstract: Effects of a diet high in fat on body weight, adiposity, and energy expenditure were investigated. Male rats were fed 8% (control) or 50% fat (by weight) for 6 mo. The high-fat group increased body weight (+26%), adipocyte size (+61%), and adipocyte number (+48%). However, food intake and resting oxygen consumption, although higher in absolute amount, were normal in that both were commensurate with the greater body mass the rats maintained. When body weight and adipocyte size were reduced by caloric restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 14 publications
5
50
0
3
Order By: Relevance
“…Food intake was not reduced by the increased leucine intake. Both we and others have observed that mice on chronic HFD become highly fuel efficient; they gain more weight per unit of calorie consumed compared with chow-fed mice (31)(32)(33)(34). In HFD-Leu mice, increased UCP3-mediated mitochondrial uncoupling of oxidative phosphorylation in thermogenic tissues likely accounts for the increased resting energy expenditure with reduced fuel efficiency.…”
Section: Discussionmentioning
confidence: 66%
“…Food intake was not reduced by the increased leucine intake. Both we and others have observed that mice on chronic HFD become highly fuel efficient; they gain more weight per unit of calorie consumed compared with chow-fed mice (31)(32)(33)(34). In HFD-Leu mice, increased UCP3-mediated mitochondrial uncoupling of oxidative phosphorylation in thermogenic tissues likely accounts for the increased resting energy expenditure with reduced fuel efficiency.…”
Section: Discussionmentioning
confidence: 66%
“…1,2 Similarly, weight-reduced obese rats quickly regain lost weight when allowed free access to food. [3][4][5][6] Weight regain in humans 7,8 and rats 9 may be partly attributable to the chronic reduction in resting metabolic rate associated with such weight loss. Some humans who successfully maintain their weight loss engage in high levels of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai determinasi (R2) sebesar 0.476 menunjukkan kaitan sebesar 47% dari penambahan konsentrasi sukrosa yang berpengaruh terhadap jarak tempuh yang dilalui tikus. Hal ini dikarenakan tikus yang diberikan pakan tinggi kalori akan mengalami peningkatan rasa tenang akibat berkurangnya stres akibat rasa lapar (Corbett et al 1986). …”
Section: Distance Traveled (Dt)unclassified
“…Menurut Corbett et al (1986) tikus yang mengalami pertambahan bobot badan dan kenaikkan asupan kalori cenderung akan mengalami penurunan aktivitas berlebih. Data ini juga ditentukan oleh faktor individu diantaranya kecepatan metabolisme, kondisi sistem endokrin, serta tingkat kecernaan pakan.…”
Section: Resting Time (Rt)unclassified